JAMA 12/11/91 (911211). (Tufts Archival Research Center, 2007)
Letter from H.E. Osmon to Mr. T.C. Griscom contending that the authors of papers and letters in an issue of the Journal of the American Medical Association (JAMA) dedicated to the topic of smoking were anti-tobacco activists. Points out that while JAMA may list the credentials of the authors, no mention of their anti-tobacco activity is listed, making it seem as though a large body of professionals support the same negative ideas on tobacco, when it is the same people who have been protesting it all along. Includes the names of the articles and the anti-tobacco activities of the author.